(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Over a period of years there has been a rapid growth in MOOC Courses, and in this context, one has to explore its effectiveness, issues and social impact. The traditional teaching-learning environment will be replaced by the free enrollment and accessibility of MOOC courses. This study explores the factors in the acceptance of learners using MOOCs, more precisely, the study analyzed learners’ acceptance of SWAYAM NPTEL MOOCs based on Four Quadrant Model and Kirkpatrick’s four level evaluation of learning model. This article also focuses on the social impact of MOOC in the teaching-learning environment. The MOOC providers have given better insight to the course providers on how to manage the platform. However, as a MOOC coordinator or respondent of one institution, one has to conduct further studies to investigate MOOCs implementation in other institutions. The outcome of this study will of course provide some insight to prospective MOOC providing institutions.